Perencanaan Strategi Pemasaran Usaha Mikro Kecil dan Menengah Manis Bakery - Tambunan, Willy; Amelia, Theresia; Priyana, Faris Prasetyohadi (Universitas Serang Raya, 2019)
Marketing is an essential aspect of the strategy of increasing product sales. Manis Bakery UMKM itself does not have a specific plan for promoting mani bread. This study aims to design the marketing strategy of UMKM Manis Bakery based on the concept of Quantitative Strategic Planning Matrix (QSPM), Competitive Profile Matrix (CPM), and Strategic Position and Action Evaluation (SPACE). This research conducted at Manis Bakery UMKM with respondents chosen were business owners and respondents who bought bread at least once a week or more. Based on the results of the analysis that has done, the results obtained that the strength possessed by the Sweet Bakery UMKM are products without preservatives, bread has a soft texture, food that is not easy to expire, strategic company location and affordable prices. The strategy is a priority based on six alternative strategies, namely creating sweet bread with flavors or innovations and making unique and attractive packaging that will do when having additional business capital.